The Development of a Care Model for the Elderly Dependency by Participation of Community Network Partners, at Sa-Ngao Sub-District health Promotion Hospital Pakchom District Loei Province - Junthod , Pennipa (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This study focuses on developing a care model for dependent elderly individuals by leveraging the participation of community network partners in the area of Ban Sa-ngao Health Promoting Hospital, Huai Phichai Subdistrict, Pak Chom District, Loei Province, Thailand. The research employed an action research methodology, using purposive sampling to select a sample group consisting of 53 home-bound and bed-bound elderly individuals with dependency and 69 stakeholders involved in developing the care model, totaling 122 participants. The research tools included workshop templates that utilized a four-step research process following the PAOR cycle, conducted in two rounds, as well as questionnaires for dependent elderly individuals and stakeholders. Data collection was carried out between June and September 2023, and the data were analyzed using descriptive statistics, including mean, standard deviation, maximum, and minimum values. The findings revealed that the care model for dependent elderly individuals, developed through the participation of community network partners, consists of four stages: 1) Planning, 2) Action, 3) Observation, and 4) Reflection. After implementing the model, it was found that the elderly participants had a high level of quality of life, with an average score of 3.83 (SD=0.12), while the stakeholders reported a very high level of satisfaction, with an average score of 4.55 (SD=0.04). The success factors of this model include: 1) strong participation of community network partners, 2) the presence of a center for the development and rehabilitation of the quality of life of the elderly, disabled, and dependent individuals in the area, 3) regular meetings and discussions among network partners, and 4) support from relevant network partners. These findings reflect that the participation of community network partners is a crucial mechanism for developing an effective care model for the elderly, which can be adapted and applied in other areas with similar contexts.